1992
DOI: 10.2527/1992.70123928x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment of selenium status of livestock2

Abstract: Assessment of the selenium status of livestock is an important aspect of production medicine, but variations in reported values between laboratories and between methods may be > 30%. Reliable interpretations require considerable experience with an assay and an extensive database from field and research case samples of a variety of species. The Michigan State University Animal Health Diagnostic Laboratory (MSU-ADHL) has offered Se analyses by acid-digestion and fluorometric detection since 1982. This laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
64
6
9

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 0 publications
10
64
6
9
Order By: Relevance
“…0.019) mmol/l. Reference values for blood Se concentrations include: ,1.52 mmol/l (Stowe and Herdt, 1992), ,1.00 mmol/l (Puls, 1994), ,0.95 mmol/l (Anderson et al, 1979), and for lamb blood Se concentrations ,0.13 mmol/l Grace and Knowles, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…0.019) mmol/l. Reference values for blood Se concentrations include: ,1.52 mmol/l (Stowe and Herdt, 1992), ,1.00 mmol/l (Puls, 1994), ,0.95 mmol/l (Anderson et al, 1979), and for lamb blood Se concentrations ,0.13 mmol/l Grace and Knowles, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Salisbury et al (1991) in their investigations of selenium concentrations in organs of slaughtered animals found 280 µg.kg -1 and 920 µg.kg -1 in bovine liver and kidney tissues, respectively. Stowe and Herdt (1992) studied dependence of selenium concentrations in blood serum on age in various animal species and reported the ranges 50 to 80 ng.ml -1 for calves and lambs and 70 to 100 ng.ml -1 for adult cattle, while the concentrations in liver tissue varied between 1200 and 2000 ng.kg -1 dry matter irrespective of the age and species of animals. Zachara et al (1993) in their studies of effects of various doses of selenium in feeds on tissue concentrations in lambs found for animals receiving the basic amount of selenium the highest concentrations in kidneys (1320 µg.kg -1 wet tissue) and the lowest in striated muscles (30 µg.kg -1 wet tissue).…”
Section: Discussionmentioning
confidence: 99%
“…These authors stated that these ratios are not constant over a range of blood Se concentrations. Stowe and Herdt (1992) quoted whole blood to serum ratios of ca. 1 in swine, 1.4-1.5 in horses and llamas, 2.5 in dairy cattle and 4 in sheep, particularly neonates, suggesting species differences in this ratio.…”
Section: Ratio Between Selenium In Whole Blood and Plasmamentioning
confidence: 99%
“…Langlands et al (1991) concluded that the two indices of Se status of the animal, whole blood and plasma Se, do not behalf similarly: Both are elevated following supplementation but thereafter plasma Se concentration falls exponentially and more rapidly than those in whole blood. Stowe and Herdt (1992) stated that this ratio would initially be narrow after an increase in oral Se intake and initially be wide on cessation of Se supplementation.…”
Section: Effects Of Dietary Composition and Source Of Seleniummentioning
confidence: 99%